All-Inorganic CsPbBr3 Perovskite Films Prepared by Single Source Thermal Ablation - Nasi, Lucia; Calestani, Davide; Mezzadri, Francesco; Mariano, Fabrizio; Listorti, Andrea; Ferro, Patrizia; Mazzeo, Marco; Mosca, Roberto (Frontiers in Chemistry, 2020)
Hybrid organo-lead halide perovskites are becoming the benchmark material for next generation photovoltaics and a very important player for other applications such as photodetectors and light emitting diodes. Nevertheless, the most important issue hindering the large-scale application of these materials remains their intrinsic instability due to the organic cation. Although the substitution with inorganic cesium (Cs) enhances stability, in most cases solution deposition methods of fully inorganic perovskites result in high surface roughness and poor surface coverage. This work reports on the evaporation of the CsPbBr3 precursor by single source thermal ablation, showing that just after deposition films consist of a mixture of CsPbBr3, CsPb2Br5, and Cs4PbBr6 due to a vertical composition gradient. We point out that mild post deposition treatments lead to the conversion of CsPb2Br5 and Cs4PbBr6 into CsPbBr3 due to its higher thermodynamic stability. Conversion results into smooth and pinhole-free CsPbBr3 films with good light absorption and emission properties. We demonstrate the suitability of obtained films for planar devices by preparing perovskite-based pure-green light emitting diodes, thus promoting Single Source Thermal Ablation as a promising alternative deposition technique for all-inorganic perovskite-based devices.